The Palestinian Delusion : The Catastrophic History of the Middle East Peace Process - Spencer, Robert (New York Bombardier Books, 2021)
Every negotiated settlement between the State of Israel and its Palestinian adversaries has failed to establish a stable and lasting peace. This is the history of what was attempted, why those failures were inevitable, and what must be done instead.
Keywords: Peace-building -- Middle East -- Arab-Israeli conflict -- Arab-Israeli conflict--Peace